Healthful eating as a manhood threat - Joseph A. Vandello; Jennifer K. Bosson; Timothy Andrew Caswell; Jenna R. Cummings (Journal of Men's Health, 2024)
Two studies test the hypotheses that men’s dietary choices are guided by the perceived genderedness of foods, men avoid feminine (but healthy) foods as a result, and that endorsing a healthy but feminine diet can be a masculinity threat. Study 1A established gendered associations about a wide range of foods and diet types by having a college student population rate the masculinity and femininity of a wide variety of foods and diet types. Study 1B surveyed university students and found that the perceived genderedness of foods predicted men’s but not women’s food preferences, even when controlling for traditional gender role endorsement and foods’ perceived healthiness. In Study 2, we experimentally tested whether a healthy but feminine diet represents a masculinity threat for men. Using a sample of college students, men and women were assigned to publicly endorse a feminine (vegetarian) or masculine (meat-based) diet. Men (but not women) who endorsed the vegetarian diet compensated by reporting stronger identification with their gender and more liking for masculine activities, and they reported being less offended by jokes that targeted feminine groups that symbolically threaten manhood (women and gay men). Collectively, these results suggest that men may compromise healthy eating habits because of manhood concerns, and endorsing healthy but feminine diets can create motivations to compensate for threatened masculinity.